2013
DOI: 10.1073/pnas.1219702110
|View full text |Cite
|
Sign up to set email alerts
|

Uracil DNA glycosylase initiates degradation of HIV-1 cDNA containing misincorporated dUTP and prevents viral integration

Abstract: Significance Misincorporation of dUTP into DNA is detrimental to eukaryotes, prokaryotes, and viruses. This study reveals the fate of uracilated HIV-1 DNA in human cells. Early stages of the viral life cycle are unaffected, but integration of uracilated viral DNA into the host genome is prevented. This effect is wholly dependent on the presence of UNG2, a nuclear enzyme that excises uracil from DNA. This study establishes that UNG2 is a restriction factor for uracilated HIV-1 DNA and explains why thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
119
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(129 citation statements)
references
References 64 publications
8
119
0
2
Order By: Relevance
“…Although HIV-1 does not encode dUTPase, its Vpr protein effectively prevents UNG2-initiated uracil excision repair (31). This alternative mechanism may allow HIV-1 to alleviative negative consequences of UNG2-mediated uracil excision and downstream pathways for the integrity of HIV-1 cDNA (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although HIV-1 does not encode dUTPase, its Vpr protein effectively prevents UNG2-initiated uracil excision repair (31). This alternative mechanism may allow HIV-1 to alleviative negative consequences of UNG2-mediated uracil excision and downstream pathways for the integrity of HIV-1 cDNA (19).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism by which Vpr mediates the induction of replication stress is unclear, it was recently linked to the Vpr-mediated recruitment of SLX4-SLX1/MUS81-EME1 structure-specific endonucleases to DCAF1, resulting in activation of the MUS81-EME1 endonuclease and, surprisingly, DCAF1-and proteasome-dependent MUS81 degradation (26). Separately, HIV-1 and HIV-2 Vpr were reported to bind a base excision repair enzyme, uracil DNA glycosylase (UNG2), which can restrict HIV-1 infection in cells with high concentrations of dUTP (19,(27)(28)(29). HIV-1 Vpr was shown to target UNG2 to the ubiquitin proteasome pathway via the CRL4 DCAF1 E3 complex and thereby disrupt UNG2-initiated base excision repair in HIV-1-infected cells (30)(31)(32).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Given our findings that dUTP is an excellent substrate, there must be undiscovered regulatory mechanisms that allow dUTP levels to persist or accumulate after the other dNTPs have been depleted. Because dUTP incorporation into HIV-1 cDNA has been implicated as a related antiviral defense mechanism (28,29), additional understanding of the mechanisms that regulate nucleotide pools during the transition from active to resting states of cells will likely be relevant to viral infectivity and persistence in these cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Work from several laboratories showed that UNG2 has a positive impact on HIV-1 (39,82,83). In contrast, some laboratories found that UNG2 hinders HIV-1 (84,85), whereas others found UNG2 to have no measurable impact on the virus (7,86). Interestingly, one work linked the requirement for UNG2 to coreceptor usage (83).…”
Section: Resultsmentioning
confidence: 99%